2012
DOI: 10.1523/jneurosci.6451-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Selective Corticospinal Tract Injury in the Rat Induces Primary Afferent Fiber Sprouting in the Spinal Cord and Hyperreflexia

Abstract: The corticospinal tract (CST) has dense contralateral and sparse ipsilateral spinal cord projections that converge with proprioceptive afferents on common spinal targets. Previous studies in adult rats indicate that the loss of dense contralateral spinal CST connections after unilateral pyramidal tract section (PTX), which models CST loss after stroke or spinal cord injury, leads to outgrowth from the spared side into the affected, ipsilateral, spinal cord. The reaction of proprioceptive afferents after this C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 82 publications
(123 reference statements)
5
125
0
1
Order By: Relevance
“…Undirected plasticity of denervated circuits leads to the development of neuronal dysfunction in the chronic stage of injury Previous investigations in animal models of SCI documented the progressive upregulation of receptor, synapse and fibre density in spinal circuitries deprived of supraspinal input (Krenz and Weaver, 1998;Kitzman, 2006;Boulenguez et al, 2010;Ichiyama et al, 2011;Kapitza et al, 2012;Tan et al, 2012;Bos et al, 2013). In the present study, we also found a multiplicity of plastic changes in spinal segments caudal to a staggered lateral hemisection SCI.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Undirected plasticity of denervated circuits leads to the development of neuronal dysfunction in the chronic stage of injury Previous investigations in animal models of SCI documented the progressive upregulation of receptor, synapse and fibre density in spinal circuitries deprived of supraspinal input (Krenz and Weaver, 1998;Kitzman, 2006;Boulenguez et al, 2010;Ichiyama et al, 2011;Kapitza et al, 2012;Tan et al, 2012;Bos et al, 2013). In the present study, we also found a multiplicity of plastic changes in spinal segments caudal to a staggered lateral hemisection SCI.…”
Section: Discussionsupporting
confidence: 81%
“…However, the regained excitability in motor neurons contributed to the development of abnormal reflex responses (Murray et al, 2010). Likewise, the depletion of corticospinal tract associated vGlut1 terminals after a pyramidotomy induced a specific sprouting of vGlut1 proprioceptive afferent fibres, but also in this condition, the synaptic reorganization adversely altered proprioceptive reflex circuits (Tan et al, 2012). Although additional mechanisms such as changes in motor neuron membrane excitability (Lin et al, 2007;Boulenguez et al, 2010) likely contribute to neuronal dysfunction in the chronic stage of SCI, our combined results suggest that undirected compensatory plasticity plays an important role in the emergence of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional perspective may be gained by characterizing the intrinsic proteomic mechanisms driving compensatory sprouting of both injured and intact CNS projections following injury (175). This includes corticospinal (176 -178), rubrospinal (179), reticulospinal, and propriospinal axons (180,181). Finally, exploring the identified signaling networks activated within injured CNS neurons that regenerate into permissive cellular grafts discussed below may yield novel insight into the molecular switches that enable growth of an axon previously incapable of regeneration.…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%